Transmission of Severe Fever with Thrombocytopenia Syndrome (SFTS) to humans: A systematic review of individual participant data and meta-analysis - Darae Woo; Ian C. Michelow; Yongyeon Choi; Hyelan Lee; Sangshin Park (Journal of Infection and Public Health)
Severe Fever with Thrombocytopenia Syndrome (SFTS) is a life-threatening emerging infectious disease caused by the SFTS virus. The aim of this systematic review and meta-analysis was to gain new insights into the routes of transmission to humans and assess whether tick bites are the dominant mechanism, as previously reported in the medical literature. Original articles were searched through Embase, Medline, and Global Health from 2009 to 2022. We performed meta-analyses to pool adjusted odds ratio (aOR) estimates using a fixed-effects model. Of 1683 articles, 41 eligible articles from three countries met the inclusion criteria, and five case-control studies were included in the meta-analysis. The most commonly reported route of transmission in the systematic review of individual participant data was person-to-person contact, particularly through exposure to blood or body fluids. Other routes included tick bites and contact with infected animals, especially cats and dogs. The meta-analysis included studies reporting transmission through human contact (n = 1), tick bites (n = 4), and animal contact (n = 1). Human contact via exposure to bodily fluids significantly increased the odds of infection (aOR: 6.27, 95 % CI: 1.23–42.81). Tick bites had a pooled aOR of 6.36 (95 % CI: 3.34–12.11). Among animal contacts, only dog contact was significant (OR: 3.60, 95 % CI: 1.04–12.51). The typical settings for SFTS transmission were human or animal hospitals, homes, and natural tick habitats. Education and effective interventions to prevent human-to-human spread, in addition to preventing transmission by tick bites, are urgently needed.